Literature Review Of Electromagnetic Actuator Force Generation For Dynamic Modal Testing Applications - Norlida, Jamil; A. R., Yusoff; M. M., Hatifi (Faculty Mechanical Engineering, UMP, 2012)
Milling is one of the most common manufacturing processes for automotive components, but its productivity is limited by the onset of regenerative chatter. This is a form of unstable self-excited vibration that occurs when the volume of material removed is too large for a particular spindle speed. This form of chatter is undesirable because it results in premature tool wear, poor surface finish on the machined component and the possibility of serious damage to the machine itself. The chatter stability of a milling process can be determined using well-established theory, provided that the frequency response of the flexible structure can be determined. In practice this usually involves the excitation of a stationery (non-rotating) milling tool with a modal hammer, and measurement of the response of the tool with a co-located accelerometer. However, this measurement is not necessarily accurate due to amplitude dependency factor consideration. There is anecdotal evidence that structural nonlinearity can have a significant effect on the chatter stability of some milling machines. This project develops non-contact electromagnetic actuators to measure the frequency response of milling tools to machine automotive parts. In addition it will describe the practical application of this approach, and discuss its amplitude dependency for current excitation during frequency response function measurement using magnetic force generation.